The Relationship between Self-Efficacy and Adherence to Drug Therapy in Hypertension Patients at the Medan Freight Health Center - Lubis, Tiffani Tantina (Asian Journal of Healthcare Analytics, 2024)
This study examines the relationship between self-efficacy and medication adherence among 83 hypertensive patients at the Sering Community Health Center in Medan. Using a cross-sectional design, self-efficacy was assessed using the General Self-Efficacy Scale, and adherence was measured through self-reported medication adherence. The findings reveal a significant positive correlation between self-efficacy and medication adherence, highlighting that patients with higher self-efficacy are more likely to adhere to prescribed treatment regimens. Duration of hypertension emerged as a significant predictor of adherence. These findings underscore the importance of psychological factors in chronic disease management and suggest that interventions aimed at enhancing self-efficacy could improve adherence and health outcomes among hypertensive patients. Future research should explore longitudinal designs to establish causal relationships and consider cultural factors in intervention strategies.